Colorectal Cancer in Northwestern Iran. (18th March 2012) - Mahmodlou, Rahim; Mohammadi, Payvand; Sepehrvand, Nariman
Abstract : Background . Colorectal cancer is the third most prevalent cancer worldwide, which is less common in the Middle East; its prevalence demonstrated to be 7 persons per 100, 000 populations in Iran. In this study, we aimed to investigate the clinicopathologic features of CRC patients in West Azerbaijan province of Iran. Methods . In this crosssectional study, 546 patients who underwent surgical procedures with the pathologic diagnosis of colorectal cancer in both academic and private hospitals of Urmia were enrolled. Results . The mean age at diagnosis was 55.2 ± 11.5 years. 23% had an age lower than forty years old. Rectal bleeding (26%), abdominal pain (25%), and large bowel obstruction (23%) were three most common presenting symptoms. 26% of patients presented with acute abdomen. 95% of tumors were adenocarcinoma, 4% were lymphoma, and 1% was other rare tumors. Regarding the stage of cancer according to TNM staging system, 6% of patients were in stage I, followed by 37% in stage II, 33% in stage III, and 24% in stage IV. In 44.5% of patients, the tumor was located in rectum. Conclusion . In west Azerbaijan province of Iran, patients with colorectal cancer present in younger age and more advanced stages in comparison with the developed countries.